Thank you for registering.

One of our academic counsellors will contact you within 1 working day.

Please check your email for login details.
MY CART (5)

Use Coupon: CART20 and get 20% off on all online Study Material

ITEM
DETAILS
MRP
DISCOUNT
FINAL PRICE
Total Price: Rs.

There are no items in this cart.
Continue Shopping

Prove that 3[sin^4(3π/2-alpha)+sin^4(3π+alpha)]-2[sin^6(π/2+alpha)+sin^6(5π-alpha)] =1. Pl send fast

Prove that 3[sin^4(3π/2-alpha)+sin^4(3π+alpha)]-2[sin^6(π/2+alpha)+sin^6(5π-alpha)] =1. Pl send fast

Grade:10

1 Answers

Jayanth Kasaraneni
50 Points
4 years ago
=3[sin^4(3π/2-alpha)+sin^4(3π+alpha)]-2[sin^6(π/2+alpha)+sin^6(5π-alpha)]=3(cos^{4}(alpha)+sin^{4}(alpha))-2(cos^{6}(alpha)+sin^{6}(alpha))
=3(1-2sin^{2}(alpha)cos^{2}(alpha))-2(1-3sin^{2}(alpha)cos^{2}(alpha))
=3-2=1

Think You Can Provide A Better Answer ?

Provide a better Answer & Earn Cool Goodies See our forum point policy

ASK QUESTION

Get your questions answered by the expert for free